Elaboração e validação de instrumento para avaliação do serviço de atendimento móvel de urgência sob a ótica do usuário - Pequeno, Gutenberg Alves (2017)
Health assessment dates to the 1910s, but only from years to years on a considered being. The SAMU 192 is a service of first necessity that allows a presence of a qualified team without place of occurrence, being triggered by free telephone with sending of suitable mobile unit to requested. As it is a service with specific characteristics and with more than 12 years of operation all over Brazil, it becomes imperative to listen to a user’s opinion a respect of their calls. With this, a main objective is to elaborate and validate an instrument capable of evaluating SAMU 192. This is a methodological development study with a method of qualitative and quantitative research methods and techniques, developed in three stages so that a First, based on the construction of a theoretical framework developed for the construction of a new evaluation instrument, being a revision in the contemporary literature, intending a solid scientific foundation capable of assisting in the elaboration process. The second stage, theoretical-practical, occupation of the process of elaboration of the items that make up the evaluation instrument based on other validated instruments, with similar objectives. In the third step, we performed the content validation, face, construction, and finally, a selection of the trustworthiness of the instrument with the elected users. The instrument is proposed for the control of the product and contemplates as dimensions the structure, processes and results, initially with 14 items, being submitted to the evaluation of experts and potential users, to perform a face and content validation so that no item was Only spelling adjustments are required. In the validation of the construct, during a first round of exploratory factorial analysis, two items presented low contribution to the evaluation instrument being excluded and performed a second round of analysis so that all items twelve items contained significant contributions to the construct in validation, confirmatory factorial analysis was confirmed, so that the values of the factorial scores of each dimension and the respective measures of Critical Relationship evidencing the convergent validity. Just as, as measures of diversity were shared with the three dimensions. All indexes were checked and evaluated per the model, the final model of the content of the abstracts. The comments are valid for their elaboration and validation, being an instrument that presents evidences of reliability. Considering that the peculiarities of the service provided by the SAMU 192, which has been received at the first moment by telephone, is then forwarded a mobile unit per needs of the applicant and, finally, the referral to a health unit with Resulting capacity in favor of an evaluation instrument valid for a reliable evaluation.